PENGARUH LIQUIDITY, LEVERAGE, PROFITABILITY DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP FIRM VALUE - Andika, Chuandry; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The main purpose of this research is to analyze the effect of liquidity, leverage, profitability, and corporate social responsibility towards firm value on listed manufacturing companies in Indonesia Stock Exchange (IDX). This research used 204 data samples consisted of 74 manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2020 period. This research used Eviews 12 in processing research data. The result obtained from this research indicates that liquidity has negative and no significant effect on firm value. Leverage has negative and significant effect on firm value. Profitability has positive and no significant effect on firm value. Corporate social responsibility has negative and no significant effect on firm value.